Wireless monitoring of water consumption in Metropolitan cities - M.Sridevi ,Dr. I. Chandra (International Journal of Advanced Science and Technology, 2020)
Now a days the water consumption is becoming more, especially in metropolitan city there is lack of awareness in usage of water every individual have no idea about the exact usage of water. The TNEB(Tamil Nadu Electric Board) is having a separate meter box in every citizen home for optimization of electricity, like electricity water is also a natural resource it is our duty to preserve it in all possible ways. In the projected system we can measure the water usage with the help of sensors namely water level sensor or ultra sonic sensor and water flow sensor, we can also had automatic switching on /off motor to avoid water overflow from tank. The collected data’s from sensors are wirelessly transmitted to mobile via Bluetooth. By using ultrasonic sensor we can measure the exact level of water in the tank. The motor turns on/off with the help of data which is collected from the ultrasonic sensors this is suitable for individual housed, when this problem comes to an apartment we can set up this water flow senor in each pipeline of respective apartment. This method can be helpful in creating awareness between people if they consume more water.